Music practice is associated with development of working memory during childhood and adolescence - Bergman Nutley, Sissela; Darki, Fahimeh; Klingberg, Torkel (Frontiers in Human Neuroscience, 2014)
Practicing a musical instrument is associated with cognitive benefits and structural brain changes in correlational and interventional trials; however the effect of musical training on cognition during childhood is still unclear. In this longitudinal study of child development we analyzed the association between musical practice and performance on reasoning, processing speed and working memory (WM) during development. Subjects (n = 352) between the ages of 6 and 25 years participated in neuropsychological assessments and neuroimaging investigations (n = 64) on two or three occasions, two years apart. Mixed model regression showed that musical practice had an overall positive association with WM capacity (visuo-spatial WM, F = 4.59, p = 0.033, Verbal WM, F = 9.69, p = 0.002), processing speed, (F = 4.91, p = 0.027) and reasoning (Raven's progressive matrices, F = 28.34, p < 0.001) across all three time points, after correcting for the effect of parental education and other after school activities Music players also had larger gray matter volume in the temporo-occipital and insular cortex (p = 0.008), areas previously reported to be related to musical notation reading. The change in WM between the time points was proportional to the weekly hours spent on music practice for both WM tests (VSWM, β = 0.351, p = 0.003, Verbal WM, β = 0.261, p = 0.006) but this was not significant for reasoning ability (β = 0.021, p = 0.090). These effects remained when controlling for parental education and other afterschool activites. In conclusion, these results indicates that music practice positively affects WM development and support the importance of practice for the development of WM during childhood and adolescence.